The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1095/biolreprod66.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Characteristics of Cloned Heifers Derived from Adult Somatic Cells1

Abstract: This study examined the onset of puberty, follicular dynamics, reproductive hormone profiles, and ability to maintain pregnancy in cloned heifers produced by somatic cell nuclear transfer. Four adult somatic cell-cloned heifers, derived from a 13-yr-old Holstein cow, were compared to 4 individual age- and weight-matched heifers produced by artificial insemination (AI). From 7 to 9 mo of age, jugular venous blood samples were collected twice weekly, and from 10 to 11 or 12 mo of age, blood sampling was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 44 publications
3
33
1
Order By: Relevance
“…Previous observations of delayed puberty in clones have already been reported by Enright et al (2002) in a limited number of females from the same set of clones. Our data confirm this observation on clones from three different genotypes.…”
Section: Discussionmentioning
confidence: 55%
“…Previous observations of delayed puberty in clones have already been reported by Enright et al (2002) in a limited number of females from the same set of clones. Our data confirm this observation on clones from three different genotypes.…”
Section: Discussionmentioning
confidence: 55%
“…Generally, follicles in the 1 st wave develop in 2-wave IOIs for 10 days, while in 3-wave IOIs it is 7 days, and the emergence of the 2 nd wave begins earlier in 3-wave IOIs and later in 2-wave IOIs (Sartori et al, 2004). The emergence of the 1 st wave in 2-wave IOIs occurs on the 2 nd day, and the ovulatory wave emerges on the 10 th day Ginther et al, 1989;Enright et al, 2002). In 3-wave IOIs the particular follicular growth waves emerge on the 2 nd , 9 th and 16 th day of IOI Ginther et al, 1989;Sartori et al, 2004;Wolfenson et al, 2004 Sartori et al (2004) found statistically conclusive differences in the emergence of the 2 nd wave between 2-wave and 3-wave IOIs in Holstein heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these clones, all derived from cumulus cells, survived and are healthy. We have studied their telomere lengths (7), expression of X-linked genes (1), onset of puberty (8), growth endocrinology (9), and behavior (10). All animal use was approved by the institutional animal care and use committees at the University of Connecticut (dairy) or the Kagoshima Prefectural Institute of Cattle Breeding and Development (beef).…”
Section: Methodsmentioning
confidence: 99%